Pengaruh Keamanan, Persepsi Risiko, dan Persepsi Kemudahan Penggunaan Terhadap Sikap Pembelian Online Shop Pada Aplikasi Lazada - Rakhmawati, Antin (Jurnal Ilmiah Administrasi Bisnis dan Inovasi, 2024)
This research aims to examine the influence of security, perceived risk, and perceived ease of use on online shop purchasing attitudes on the Lazada application (Study of Lazada application users in Malang City). This research is quantitative in nature and primary data consists of filling out a questionnaire taken using the Machin and Champbell formula for 106 respondents. The data collection technique used in this research is a questionnaire by collecting data through an online survey and then processing it using multiple linear analysis using the SPSS 20.00 for Windows Executed application. The results of this research show that all variables, namely security, perceived risk and perceived ease of use have a positive influence on purchasing attitudes.